Knit of the living dead - Ehrhart, Peggy (Ehrhart, Peggy. Knit & Nibble mystery, 2020)
"Among the countless revelers at the town's much-anticipated Halloween parade, a woman dressed as Little Bo Peep is the only one making people scream bloody murder. In a scene straight out of a horror movie, the Knit and Nibblers find the nursery rhyme character dead with thick strands of yarn looped around her neck. Pamela and her best friend, Bettina, are set on pinning down who wanted the woman gone forever, but it'll take every trick they can muster to catch the culprit without becoming the next poor souls to join Little Bo Peep's dark, endless sleep ..."--